SENA´s challenges within the tertiary education in Colombia - Álvarez Fonseca, Lida Yamile
The paper reports what the tertiary education is, describes how it is currently considering higher education in Colombia, using statistics of higher education in the country, highlighting the role of education for work and human development and it ends with a series of perspectives on the challenges posed by the current policy in Colombia.